The Application of Google Classroom as Media for Teaching and Learning - Muhammad Hassan (The Seall Journal, 2021)
Teaching and learning activities in the class for English teaching materiel is one of the challenging in higher education. Subject that is most practical activities such as listening and speaking are by illustrative or demonstrative in the class that emphasize the acquisition of observational skills; and allow students to see the concept dealt in action and relate theory more closely to reality. However, the students’ reaction to practical the conversation or dialogue, they are not effective in class and this may reflect a student perception that there is lack of clear purpose. The main objective of this study is to explore the effectiveness of Google Classroom’s active learning activities for listening and speaking subject under the Decision class program. A set of questionnaires has been distributed to a sample of 100 students who enrolled listening and speaking subject were used in this study. The analysis of the data was carried out using Technology Acceptance Model (TAM) to examine the relationship between the identified factors and the effectiveness of the learning activities. The results prove that majority of the students satisfy with the Google Classroom’s media that were introduced in the class where all ratios are above averages. In particular, comparative performance is good in the areas of ease of access, perceived usefulness, communication and interaction, instruction delivery and students’ satisfaction towards the Google Classroom as media in teaching and learning activities.